Power plant instrumentation and control handbook a guide to thermal power plants - Basu, Swapan (Academic Press is an imprint of Elsevier, 2015)
The book discusses instrumentation and control in modern fossil fuel power plants, with an emphasis on selecting the most appropriate systems subject to constraints engineers have for their projects. It provides all the plant process and design details, including specification sheets and standards currently followed in the plant. Among the unique features of the book are the inclusion of control loop strategies and BMS/FSSS step by step logic, coverage of analytical instruments and technologies for pollution and energy savings, and coverage of the trends toward filed bus systems and integration of subsystems into one network with the help of embedded controllers and OPC interfaces. The book includes comprehensive listings of operating values and ranges of parameters for temperature, pressure, flow, level, etc of a typical 250/500 MW thermal power plant. Appropriate for project engineers as well as instrumentation/control engineers, the book also includes tables, charts, and figures from real-life projects around the world"